Probiotic Cocktail Alleviates Intestinal Inflammation Through Improving Gut Microbiota and Metabolites in Colitis Mice - Zhu, Yefei; Xu, Yu; Wang, Xinyue; Rao, Leiping; Yan, Xuebing; Gao, Renyuan; Shen, Tongyi; Zhou, Yuan; Kong, Cheng; Zhou, Longxiang (Frontiers in Cellular and Infection Microbiology, 2022)
The modulation of the gut microbiome has been widely suggested as a promising therapeutic strategy for inflammatory bowel disease (IBD). Here, we established a novel probiotic cocktail to investigate its therapeutic role in acute colitis mice. During dextran sulfate sodium (DSS)-induced colitis, the mice were treated with the probiotic cocktail, fecal microbiota transplantation (FMT) from a healthy mice donor, or 5-aminosalicylic acid (5-ASA), respectively. The inflammatory responses were assessed by symptoms, serum inflammatory factors, and histological scoring. The intestinal barrier function was assessed by detecting tight junction proteins. Gut microbiota and its metabolites were further identified using 16S rDNA sequencing and a liquid chromatograph mass spectrometer (LC-MS/MS). Compared with FMT and 5-ASA treatment, the probiotic cocktail performed better in alleviating symptoms of colitis and decreasing disease activity score and mucosal inflammation. The probiotic cocktail also significantly decreased serum IL-17 level and increased JAM-1 expression in colon. The gut microbiota analysis confirmed that the beneficial effects of the probiotic cocktail were attributed to increasing anti-inflammatory bacteria Akkermansia, Bifidobacterium, and Blautia, while decreasing pro-inflammatory bacteria Parasutterella. The targeted metabolome analysis further indicated a rise in the production of Bifidobacterium-related short-chain fatty acids (SCFAs) such as propanoic acid and isobutyric acid after probiotics treatment. Taken together, the probiotic cocktail effectively alleviated intestinal inflammation through improving gut microbiota and metabolites in colitis mice, suggesting its great potential to be a novel therapeutic approach for IBD patients.